ANALISIS KEBUTUHAN PENGEMBANGAN WEBSITE MATERI PERSEBARAN MEGALITIKUM PADA MATA KULIAH SEJARAH LOKAL DI SUMATERA SELATAN - syarifuddin syukur; Umi Chotimah; Rhaptyalyani Herno Della; Suratmi Suratmi; Seruni Seruni; Intan Permatasari; Dwi Putri Selvita Sari Selvita Sari (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2024)
This research aims to conduct a needs analysis of website learning resources for material on the distribution of megaliths in local history courses in South Sumatra. Technological advances have a significant impact on life that cannot be avoided, because science and technology has many benefits that make human work easier quickly and practically. Science and technology has a big influence in various fields, one of which is education. Education really needs new innovations in the form of technology created to improve the quality and quality of students. At this stage the researcher collected data related to learning resources on megalithic distribution websites in the local history course. The research method chosen in this research is research and development (R&D). The subjects in this research were 234 History Education students. This research uses descriptive qualitative research methods. Researchers distributed questionnaires to students via Google Forms. The data analysis technique used by researchers is interactive data analysis technique. Based on the results of the questionnaire, it was found that 50.4% of students stated the importance of learning local history, 51.7% needed local history learning resources, 64.5% liked audiovisual media, 66.2% had internet access, 99.1% needed websites and 50. 9% need a video feature on the website. Therefore, to help improve the quality of learning, website learning resources are an alternative.